A new species of Parapercis (Teleostei: Pinguipedidae) from Madagascar - Sparks, John S.; Baldwin, Zachary H. (Zootaxa, 2012)
A new species of sandperch is described from the shallow nearshore reefs of the Masoala Peninsula, northeastern Mada-gascar. The new species is distinguished from congeners occurring in the region by a unique pigmentation pattern on thecaudal fin comprising two large, oblong black blotches, with the smaller of the two markings located dorsally near the finbase and a much larger and more elongate patch situated ventrally, as well as the presence of numerous smaller blackblotches forming two to three bands distally on the caudal membrane, two longitudinal series of six to nine prominentblack blotches on the mid and lower flank, and the presence of large diffuse dark brown blotches on the snout, lips, cheek and opercle.